(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The traditional, age-old Indian medical system known as Ayurveda encompasses a wide range of fundamental ideas. The five natural elements in the Panchmahabhautika Chikitsa Siddhanta are Prithvi (earth), Jala (water), Akasha (space), Agni (fire), and Vayu (air). All of these substances contain chemicals, minerals, and nutrients that might enhance health and are related to the potential of human life on Earth. One of these, Mrittika, is among the most crucial components and is rich in nutrients that are crucial to human health. Shothahara and Shoolhara Gunas, according to the Acharyas. It is highly helpful in treating and preventing many ailments since it can remove toxins from the human body. The Ayurvedic Samhitas provide a thorough explanation of Mrittika’s exterior and interior uses under Parthiva Chikitsa. It is highly helpful in treating and preventing many ailments since it can remove toxins from the human body. This article, explains the beneficial properties of Mrittika.